2018 International Joint Conference on Neural Networks (IJCNN) 2018
DOI: 10.1109/ijcnn.2018.8489260
|View full text |Cite
|
Sign up to set email alerts
|

McDiarmid Drift Detection Methods for Evolving Data Streams

Abstract: Increasingly, Internet of Things (IoT) domains, such as sensor networks, smart cities, and social networks, generate vast amounts of data. Such data are not only unbounded and rapidly evolving. Rather, the content thereof dynamically evolves over time, often in unforeseen ways. These variations are due to so-called concept drifts, caused by changes in the underlying data generation mechanisms. In a classification setting, concept drift causes the previously learned models to become inaccurate, unsafe and even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…They found that the focus on evolved classes may damage the results for nonevolved classes. The authors in [16] assigned higher weights to new instances for faster detection of concept drifts. In [17], the authors introduced the Fast Hoeffding Drift Detection Method that uses a sliding window and Hoeffding's inequality which enables the detection of drifts with a shorter delay.…”
Section: Related Workmentioning
confidence: 99%
“…They found that the focus on evolved classes may damage the results for nonevolved classes. The authors in [16] assigned higher weights to new instances for faster detection of concept drifts. In [17], the authors introduced the Fast Hoeffding Drift Detection Method that uses a sliding window and Hoeffding's inequality which enables the detection of drifts with a shorter delay.…”
Section: Related Workmentioning
confidence: 99%
“…The first class comprises detectors that use statistical tests, such as the Cumulative Sum and the Page-Hinckley Test (Page, 1954). This group includes DDM (Gama et al, 2014), EDDM (Baena-García et al, 2006), and the McDiarmid drift detection method (Pesaranghader, Viktor, & Paquet, 2018). The second class includes window-based methods, which, in general, monitor the accuracy of the classifier for instances in a window.…”
Section: Taxonomymentioning
confidence: 99%
“…Concept drift [24,25] describes the problem of sample distributions that change over time. This can be an abrupt event in the data stream, but it also can be a gradual, reoccurring or even virtual process [26]. Gomes et al [27] mention other possible research directions within incremental learning like anomaly detection [28], ensemble learning, recurrent neural networks and reinforcement learning.…”
Section: Related Workmentioning
confidence: 99%